1987
DOI: 10.1136/ard.46.11.830
|View full text |Cite
|
Sign up to set email alerts
|

Iliac crest trabecular bone mass and structure in patients with non-steroid treated rheumatoid arthritis.

Abstract: SUMMARY Iliac crest trabecular bone volume and structure have been studied in bone biopsy specimens from 48 patients with classical or definite rheumatoid arthritis, none of whom had received steroids. Results were compared with those obtained from healthy controls matched for age and sex. The mean trabecular bone volume in female patients aged 34-50 years was significantly lower than in controls (p Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 22 publications
0
22
0
1
Order By: Relevance
“…We have also used, as reference values, those derived from iliac crest specimens of 16 individuals aged 16-49 years who died in the Intensive Care Unit of our Hospital (Hospital Universitario de Canarias, Tenerife) of injuries from traffic accidents and were selected as kidney donors. We also used data reported by several investigators (Merz and Schenk, 1969;Meunier et al, 1972;Bordier and Tun Chot, 1969;Courpron et al, 1971;Croucher et al, 1994;Mellish et al, 1987;Dahl et al, 1988;Ballanti et al, 1990). Some of these results are shown in Table 2.…”
Section: Bone Histomorphometrymentioning
confidence: 80%
“…We have also used, as reference values, those derived from iliac crest specimens of 16 individuals aged 16-49 years who died in the Intensive Care Unit of our Hospital (Hospital Universitario de Canarias, Tenerife) of injuries from traffic accidents and were selected as kidney donors. We also used data reported by several investigators (Merz and Schenk, 1969;Meunier et al, 1972;Bordier and Tun Chot, 1969;Courpron et al, 1971;Croucher et al, 1994;Mellish et al, 1987;Dahl et al, 1988;Ballanti et al, 1990). Some of these results are shown in Table 2.…”
Section: Bone Histomorphometrymentioning
confidence: 80%
“…These pathological changes resulted from a profile of increased plasma levels of the proinflammatory cytokines Interleukin-2, which was thought to play an important role in the pathogenesis of RA [9]. Besides, T cells initiated the inflammatory cascade through secretion of IL-2 that was higher in the long-lasting RA [10]. Preliminary studies in our laboratory showed that I. serra extracts inhibited the proliferation of mitogen-stimulated cultures of murine splenic T lymphocytes in vitro.…”
Section: Discussionmentioning
confidence: 94%
“…IL-2 is mostly produced by mature T lymphocytes and could increase the proliferation of lymphocytes and activate the secretion of lymphokines. It was reported that IL-2 level is increased in blood serum, synovial fluid and lymphocytes serum of arthrosis autoimmune disease patients [9,10]. IFN-γ could increase the identification and submission to autoantigen for inducing T cells.…”
Section: Introductionmentioning
confidence: 98%
“…Chief among these is the action of corticosteroids in patients treated for chronic inflammatory conditions such as asthma or rheumatoid arthritis, which are known to cause homogeneous thinning of the trabeculae (130). Similarly, cytokines such as TNF-a, which are elevated in rheumatoid arthritis, cause bone loss in the form of TB thinning (131).…”
Section: D Structure Analysismentioning
confidence: 99%